High incidence of chromosomal imbalances and gene amplifications in the classical follicular variant of follicle center lymphoma - Bentz, Martin; Werner, Claudius Alexander; Döhner, Hartmut; Joos, Stefan; Barth, Thomas F. E.; Siebert, Reiner; Schröder, Martin; Stilgenbauer, Stephan; Döhner, Konstanze; Möller, Peter; Lichter, Peter (Blood, 1996)
The classical follicular variant of follicle center lymphoma (FCL-fo) is associated with the chromosomal translocation t(14; 18)(q32;q21). However, the sole presence of this translocation is not sufficient for malignant transformation, as demonstrated by experiments in a transgenic mouse model. Most of the secondary changes, which play a central role in tumor development and progression and which are presumed to be of prognostic value, are gains and losses of chromosomal material. We analyzed 28 FCL-fo patients using comparative genomic hybridization (CGH). The most frequent imbalances were gains on chromosomes X, 7, 8, 12, and 18 as well as losses of material on chromosome arm 6q. For chromosomes X, 8,12, and 18, the CGH data allowed further narrowing of the relevant subregions. In addition, novel high-level DNA amplifications were identified in five instances mapping to chromosome bands 1p36, 6p21, 8q24 (2 patients), and 12q13-14. Previously, such amplifications have been identified very rarely in lymphomas. In the 2 patients with amplifications mapping to chromosomal band 8q24, involvement of the MYC proto-oncogene in the amplification unit was demonstrated by Southern blot analysis. These data provide further entry points for studies to identify genes relevant for tumor progression in FCL-fo.